Accuracy of Endoscopic Ultrasound (EUS) in T-Staging of Ampullary Tumors - Azar, Riad R. (2011)
EUS is routinely used for confirming the diagnosis and staging ampullary tumors. EUS staging helps to identify patients optimal candidates for endoscopic ampullectomy and avoid surgery in this group or those with unresectable disease. The reported accuracy of EUS staging of ampullary cancer has been variable.